PENERAPAN MODEL PEMBELAJARAN EXPERIENTIAL LEARNING DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMAN 2 SETU KABUPATEN BEKASI - Nadya Elvita Refiardani; Slamet Triyadi; Sutri Sutri (Universitas Muhammadiyah Surabaya, 2025)
The skill that is currently still difficult for students to master in Indonesian language learning is writing skills. This research aims to describe the implementation of the experiential learning model in improving the writing ability of negotiation texts for grade X students of SMAN 2 Setu, Bekasi Regency. This study uses a quantitative approach with a quasi-experimental method. The sampling technique in this study is purposive sampling. The sample used is class X 1 as the experimental group and class X 7 as the control group. Data collection techniques in this study consist of interviews, tests, questionnaires, and documentation. The instrument used is one essay question. The learning activities in the experimental class use the experiential learning model. Based on the results of hypothesis analysis, the significance value < 0.001 < 0.05 shows a significant difference between the experimental and control classes. This means that H0 is rejected and H1 is accepted. Furthermore, the experimental class achieved a higher mean score, namely 79.85 compared to the control class which only scored 57.35. The improvement observed in this study can be seen from the ability of the experimental class students to write negotiation texts after applying the experiential learning model. The experimental class students were able to write negotiation texts by paying attention to the relevance of content; the use of capital letters, spelling, and punctuation; the characteristics of negotiation texts; the structure of negotiation texts; as well as considering the linguistic elements of negotiation texts compared to the control class.